CUSTOMER-PERCEIVED VALUE IN CREATING CUSTOMER SATISFACTION AND REVISIT INTENTION IN SHARIA HOTELS - Adirestuty, Fitranty (Journal of Islamic Monetary Economics and Finance, 2019)
The purpose of this study was to identify the relationship between Islamic servicequality, Muslim Customer Perceived Value (MCPV), customer satisfaction, and revisitintention on sharia hotels in Bandung. A systematic random sampling was used todraw sample of 255 customers. The hotel includes Orange Home Sharia, ShariaNarapati Hotel, Cottage Daarul Jannah, Daarul Mutmainah, and MQ Guest House.This research used Structural Equation Modeling to measure the variables of servicequality (Gayatri, 2013) and Muslims Customer Perceived Value (MCPV) (Eid andGohary, 2015) to measure the perceived value variables. Eleven hypotheses weredeveloped and tested using a sample of 255 Muslim tourists. Exploratory andconfirmatory factor analysis was used to test the validity of the measures, while thestructural equation modeling in hypotheses testing. The strength of the relationshipbetween the constructs indicates that features of the suggested MCPV model are crucialto achieving Muslim customer retention in the tourism industry. Findings also suggestthat the availability of the suggested Islamic attributes value, along with conventionalvalue dimensions, could satisfy Muslim tourists when they buy a tourism package